2015
DOI: 10.1186/s13046-015-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of antiviral drugs targeting chemorefractory colorectal adenocarcinoma cells overexpressing endogenous retroviral elements

Abstract: BackgroundEndoretroviruses account for circa 8 % of all transposable elements found in the genome of humans and other animals. They represent a genetic footprint of ancestral germ-cell infections of exoviruses that is transmittable to the progeny by Mendelian segregation. Traces of human endogenous retroviruses are physiologically expressed in ovarial, testicular and placental tissues as well as in stem cells. In addition, a number of these fossil viral elements have also been related to carcinogenesis. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 41 publications
2
47
0
1
Order By: Relevance
“…Diaz-Carballo et al . tested the antiviral drugs, amantadine and pleconaril, which target HERV components expressed in chemotherapy-naïve and chemoresistant CRC cell lines [ 63 ]. The mechanism of action of both medications is still poorly understood.…”
Section: Selected Repurposing Candidates For the Treatment And/or Prementioning
confidence: 99%
“…Diaz-Carballo et al . tested the antiviral drugs, amantadine and pleconaril, which target HERV components expressed in chemotherapy-naïve and chemoresistant CRC cell lines [ 63 ]. The mechanism of action of both medications is still poorly understood.…”
Section: Selected Repurposing Candidates For the Treatment And/or Prementioning
confidence: 99%
“…Both treatments are known to influence HERV transcription with no specificity for tumor environment [ 78 ]. Similarly, Díaz-Caballo et al reported a HERV-W hyperexpression in HCT8 colon carcinoma cells, and proposed a correlation with the induction of a chemotherapy-refractory state [ 77 ]. Such increased transcription, however, is possibly the consequence of the experimental induction of a cytostatic stress.…”
Section: Herv-w Expression In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
“…This scenario can provide the rationale for inclusion of HERV-H Xp22.3 into clinical vaccination protocols. A study conducted by Díaz-Carballo et al 119 demonstrated that the expression of various HERVs proteins was not only detectable in colon cancer cells but might also have therapeutic implications for the patients, especially in chemorefractory tumors. In particular, several retroviral transcripts resulted overexpressed in HCT8 colon cancer cell line up to three times in chemotherapy refractory HCT8 cells, suggesting a relationship to chemoresistance.…”
Section: Immunotherapy Of Hervs-positive Colon Cancermentioning
confidence: 99%
“…This evidence proposed the HERVs' overexpression as a tool for monitoring the therapy resistance. 119 Bronte et al 120 reported that the inoculation of a DNA plasmid encoding mouse gp70 or p15E (two products of the env gene of an endogenous murine leukemia virus) elicited the T-lymphocyte response and resulted in partial protection of the mouse tumors possessing these antigens. Furthermore, systemic administration of agonistic anti-CD40 monoclonal antibodies increased the therapeutic potential of the DNA vaccine uniquely when administrated during the tumor rejection phase.…”
Section: Immunotherapy Of Hervs-positive Colon Cancermentioning
confidence: 99%